Inhibition of arsenite methylation induces synergistic genotoxicity of arsenite and benzo(a)pyrene diol epoxide in SCC-7 cells. Issue 1 (15th November 2018) - Li, Youxian; He, Man; Chen, Beibei; Hu, Bin
Abstract : A comprehensive analytical method was developed to investigate the synergistic genotoxicity of BPDE and As(iii ) in SCC-7 cells. Abstract : As is well-known, arsenite (As(iii )) is a human carcinogen associated with many human cancers. As(iii ) can act as a co-carcinogen to induce DNA damage with other carcinogens. Benzo( a )pyrene diol epoxide (BPDE) is one of the most-studied environmental carcinogens, which exists ubiquitously in our daily life. The elucidation of the mechanism of As(iii ) as a co-carcinogen with BDPE in cells causing genotoxicity is beneficial for the evaluation of its bioeffect. In this study, a comprehensive analytical system is used for DNA damage evaluation, BPDE–DNA adduct detection, arsenic speciation and gene expression analysis. Based on the experimental results, it can be inferred that BPDE and As(iii ) synergistically cause genotoxicity, and the possible mechanism is that BPDE inhibits arsenic methylation, leading to cellular As(iii ) enrichment. As(iii ) inhibits nucleotide excision repair (NER) of the DNA adduct damage caused by BPDE. The synergistic effect of BPDE and As(iii ) causes DNA strand break damage, which further results in carcinogenesis.